Inhibition of Tissue Activator by Urokinase Inhibitor - Kawano, T; Uemura, Y (Thrombosis and Haemostasis, 1971)
Inhibition of tissue activator purified from human heart by urokinase inhibitor purified from human placenta was observed by both the fibrin plate method and fibrin clot lysis time method. It was shown to be of much less on extent in comparison with urokinase, that is, 20 Ploug units of urokinase were completely inhibited by approximately 100 or 200 u of urokinase inhibitor in the respective methods but 6 Ploug units of tissue activator were inhibited only 25% to 50% even though 1,000 u of urokinase inhibitor were used.